A Case of Epstein-Barr Virus-Associated Peripheral T-Cell Lymphoma - NAYA, Mayumi; SAWADA, Tadashi; HIBI, Shigeyoshi; TABATA, Yasuhiro; KIHARA, Akio; IMASHUKU, Shinsaku; OSAWA, Minako; TODO, Shinjiro; NAKABAYASHI, Yoshinobu; HOJO, Makoto (The Japanese Journal of Pediatric Hematology, 1997)
A 4-year-old girl developed Epstein-Barr virus (EBV) -associated peripheral T-cell lymphoma (PTCL), showing hemophagocytic lymphohistiocytosis. Bone marrow smears showed an increase of atypical immuno-blasts with mature T-cell antigens and some histiocytic hemophagocytes. Southern blot analyses of bone marrow cells by TCR C-β-1 and EBV terminal probes revealed the monoclonal proliferation of EBV-infected T-cells. The patient received HLH-94 protocol and achieved remission in a month. At 50 days after the onset, however, the disease recurred. Combined chemotherapy with cyclosporin A improved her condition transiently. At the 7th month, she received an allogeneic bone marrow transplantation (BMT) from her HLA-identical brother. She is doing well 6 months after the transplantation. It is suggested that allogeneic BMT is an effective treatment for refractory EBV/PTCL.